Monetary Union, EU financial transfers and regional integration: The Spanish case - Jose Maria Mella; Maria Asuncion Lopez (European Regional Science Association (ERSA), 1998)
According to the best established economic theories, the monetary union does not spontaneously guarantee a catching-up process ("real convergence") among the member states in terms of well-being economic level. On the contrary, the monetary unification can increase the income disparities among countries and regions, if there are not strong compensation policies which help the least developed territorial economies to make an effort of a more intense investment in order to achieve greater production growth rates. Concerning the "real convergence" of the Spanish regions and economy, we must take into account that -according to the new economic theories of the endogenous growth- the infrastructures, the human and technological capital, and other intangible assets require the support of the public investment and the EU budget. This support is particularly important in countries like Spain, where the relative productivity level and the GDP per head are still far below the European average. Therefore, our attention will be focused on three points. In the first place, we are going to analyze the cohesion problem in Spain in the European framework. Secondly, we are going to survey some inconsistencies of the EU budget bearing in mind the real convergence target. And finally, we are going to make some reflections of economic and regional policy taking into account the enlargement of the EU to the east and central European countries in the next future (Agenda 2000).
Keywords: 330